Understanding fragility: implications for global health research and practice. Issue 2 (10th December 2019) - Diaconu, Karin; Falconer, Jennifer; Vidal, Nicole; O'May, Fiona; Azasi, Esther; Elimian, Kelly; Bou-Orm, Ibrahim; Sarb, Cristina; Witter, Sophie; Ager, Alastair
Abstract: Advances in population health outcomes risk being slowed—and potentially reversed—by a range of threats increasingly presented as 'fragility'. Widely used and critiqued within the development arena, the concept is increasingly used in the field of global health, where its relationship to population health, health service delivery, access and utilization is poorly specified. We present the first scoping review seeking to clarify the meaning, definitions and applications of the term in the global health literature. Adopting the theoretical framework of concept analysis, 10 bibliographic and grey literature sources, and five key journals, were searched to retrieve documents relating to fragility and health. Reviewers screened titles and abstracts and retained documents applying the term fragility in relation to health systems, services, health outcomes and population or community health. Data were extracted according to the protocol; all documents underwent bibliometric analysis. Narrative synthesis was then used to identify defining attributes of the concept in the field of global health. A total of 377 documents met inclusion criteria. There has been an exponential increase in applications of the concept in published literature over the last 10 years. Formal definitions of the term continue to be focused on the characteristics of 'fragile and conflict-affected states'. However, synthesis indicates diverse use of the concept with respect to: level of application (e.g. from state to local community); emphasis on particular antecedent stressors (including factors beyond conflict and weak governance); and focus on health system or community resources (with an increasing tendency to focus on the interface between two). Amongst several themes identified, trust is noted as a key locus of fragility at this interface, with critical implications for health seeking, service utilization and health system and community resilience.